Technical Evaluation and Boezem Bratang Operation Patterns In Surabaya - Akhmad Lutfis Salamin (NAROTAMA UNIVERSITY, Indonesia)
Surabaya is the second largest and most populous city in Indonesia and is inseparable from the problem of flooding which is still flooded the area of East Surabaya.Flooding is caused by Bratang boezem unable to accommodate rainwater discharge. Boeang Surabaya has an area of 19,900 m2, has two systems namely flood gates and flood pumps. The floodgate system will work to drain the boezem bratang water to wonokromo river if the water elevation at Wonokromo River is at under the elevation of Bratang boezem water and flow Gravitatively while the pump system will work if the floodgate system is no longer functioning. To overcome the problem of flooding in the region, it is necessary to conduct hydrological and hydraulics analysis by performing boezem routing to determine the Boezem capacity whether it can accept the planned rain discharge. a depth of 3 m is unable to accommodate a maximum flood discharge period of 2.5 and 10 years. so it is planned to increase the boezem depth which was originally 3 m to 4.6 m, and increase the pump capacity which was originally from 10.5 m3 / s to 14 m3 / s.From the plan, after the hydrologic and hydraulics analysis using Boezem routing, Boezem has been able to accommodate the planned rain discharge.